Gram-negative bacilli from the Enterobacteriaceae family. β-Lactamases with extended substrate spectrum (ESBL) – characteristics, selected molecular aspects of antibiotic resistance, diagnostics – short literature review - Likus, Paulina; Magdalena Greczek-Stachura; Anna Macieja (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2024)
The Enterobacteriaceae family includes various types of Gram-negative bacteria. Microorganisms treated with antibiotics modify “resistance mechanisms”. An example is selected bacteria from the Enterobacteriaceae family, strains of which can produce extended-spectrum β-lactamases (ESBLs). β-lactamases are enzymes that can hydrolyse penicillins, cephalosporins (including third- and fourth-generation, C3G and C4G) and aztreonam, resulting in the development of infection, and fewer therapeutic options. Diagnosis is impeded by the presence of different phenotypes of ESBL resistance to β-lactamases. It leads to detailed substrate preferences of specific ESBL types, designated inhibitor sensitivity, and degree of enzymatic activity and expression, providing the basis for several identification steps. A single mutation in the active site of the enzyme led to the formation of known ESBLs (TEM-1, TEM-2 and SHV-1). Newer enzymes (CTX-M) are derived from cephalosporinases produced by certain plant bacterial strains (e.g. Kluyvera ascorbata), which are then inserted into mobile genetic elements. To date, more than 350 different ESBL enzymes have been identified.